In Search of the Human. The Work of the Dardenne Brothers From Social Criticism to Hope. The Cinema of the Dardenne Brothers - Sofia Sjö (Journal for Religion, Film and Media, 2016)
Close-ups of human faces and hands, shots that are anchored around human individuals, with landscapes or cityscapes only present in so far as they represent the environment in which these individuals live and act, a camera that moves and breathes with human bodies, scenes defined by the actions and interactions of the characters, narratives of human despair and resilience, broken relationships and offers of trust - without wanting to delimit the multifaceted oeuvre of Belgian filmmakers Jean-Pierre and Luc Dardenne, these prominent aesthetic and narrative elements of their films underline one central theme across their work, the search for the human. What is the human being? What are the conditions that hinder or promote human flourishing? How can human beings exist in an industrialized, technicized society? How can they maintain their humanity under dehumanizing conditions? These questions are not explicitly religious, let alone specific to Christianity, and they are treated in the films of the Dardennes without direct reference to religious traditions and their bids to make sense of human existence.